2015
DOI: 10.1155/2015/439520
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Radiative Heat Transfer in Oxy-Methane Flame Simulations: An Examination of Its Sensitivities to Chemistry and Radiative Property Models

Abstract: Measurements from confined, laminar oxy-methane flames at different O2/CO2dilution ratios in the oxidizer are first reported with measurements from methane-air flames included for comparison. Simulations of these flames employing appropriate chemistry and radiative property modeling options were performed to garner insights into the experimental trends and assess prediction sensitivities to the choice of modeling options. The chemistry was modeled employing a mixture-fraction based approach, Eddy dissipation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Figure 2a provides the geometric details of the furnace simulated in this study. Experimental measurements and numerical simulation of methane flames in this geometry at different O 2 /CO 2 dilution ratios in the oxidizer stream have been reported in several studies [7,10,13,19]. However, results from 100% O 2 -methane flames have not yet been reported and were simulated in this study for a range of fuel inlet Reynolds numbers (2600-14,000).…”
Section: Reference Solution Using Slw Modelmentioning
confidence: 87%
See 4 more Smart Citations
“…Figure 2a provides the geometric details of the furnace simulated in this study. Experimental measurements and numerical simulation of methane flames in this geometry at different O 2 /CO 2 dilution ratios in the oxidizer stream have been reported in several studies [7,10,13,19]. However, results from 100% O 2 -methane flames have not yet been reported and were simulated in this study for a range of fuel inlet Reynolds numbers (2600-14,000).…”
Section: Reference Solution Using Slw Modelmentioning
confidence: 87%
“…In order to assess the prediction sensitivities to the uncertainties in the thermal boundary condition, the calculations in Cases 1-4 were repeated at wall temperatures of 500 and 700 K employing the SLW model. The wall temperature range 300-700 K investigated in this study is representative of those found in enclosed environments burning oxymethane flames [7,10,13,19]. The sensitivity of the centerline (0, 0, z) radiative source term (-r•q) prediction to the wall temperature is shown in Fig.…”
Section: Sensitivity To Wall Temperature (Epistemic Uncertainty)mentioning
confidence: 95%
See 3 more Smart Citations